Optimasi Tata Letak Gudang Menggunakan Metode Shared Storage Berbasis Analisis ABC dan Jarak Rectilinear pada CV. XYZ - Hakim, Rizki; Okitasari, Hanissa (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study evaluates warehouse layout performance improvement at CV. XYZ by applying shared storage integrated with ABC analysis and rectilinear distance to minimize material handling distance. A quantitative descriptive comparative approach was employed using movement frequency and slot distance data for 12 product types. ABC classification establishes activity priority, while rectilinear distance guides dynamic slot allocation based on proximity. The results show a reduction in total material handling distance from 6,720 m to 5,280 m, equivalent to a 21.4% efficiency improvement. The contribution lies in integrating activity-based classification and distance optimization within a flexible storage scheme that outperforms static approaches. Implementation requires accurate recording systems and the inclusion of additional operational variables to improve robustness.